O que dizem os professores sobre alfabetização e letramento numa perspectiva interdisciplinar. - Silva, Josivaldo Barbosa da (2024)
Literacy and literacy represent processes that must include actions that make it possible to teach with meaning for the child, so that reading and writing are not just a way of decoding words, but rather a way of deriving meaning from what is written, so that the same process is practiced in concrete situations of society. For this, it is necessary to teach literacy within the context of interdisciplinarity. Based on this, the present study aimed to analyze the knowledge and practice of teachers in questions related to literacy and literacy in an interdisciplinary perspective. The research method used was qualitative, exploratory and descriptive and data collection involved bibliographical and field research. The bibliographical research focused on substantiating the historical process of knowledge about literacy that involves the dialogue between the educational field and that of language with the theme of interdisciplinarity. The field research was carried out through case studies, based on semi-structured interviews with teachers of the 1st year of elementary education in the municipal education network of Recife (PE), aiming to understand the incursion of teachers into literacy and literacy from a perspective interdisciplinary. The results indicated that most of the participants in this research do not use interdisciplinary practices in the context of literacy and literacy, or do so without any planning and unrelated to current theories of literacy. Most make use of traditional literacy methods and often do not know their meaning.